Identifikasi Keanekaragaman Palem (arecaceae) Di Taman Wisata Alam Sorong Distrik Klaurung Kota Sorong - serkadifat, yetty; Wattimena, Lanny; osok, yonace (Median : Jurnal Ilmu Ilmu Eksakta, 2025)
The Nature Tourism Park (TWA) area has the potential for abundant and diverse flora and fauna, one of the types found in the area is palm. Palm is one of the components that make up forest vegetation in TWA Sorong which also has a very important role. This study aims to find out the types of palms (arecaceae) and their diversity index in TWA Sorong. The research was carried out using the exploratory survey method in the Sorong Nature Tourism Park with 4 transect paths with an area of 1 Ha. The results of the study showed the discovery of 17 types of palms consisting of 15 types of palms and 2 types of rattan. In addition, the level of palm species diversity (H') is classified as moderate with an H' value of 1.526 (1< H'< 3) and a species evenness with a value of E = 0.398 so it is included in the medium category.